Estimasi Demand Angkutan Barang Shortcut Padang – Solok dari Peralihan Moda Truk ke Kereta Api Sebagai Bahan Pertimbangan Proyek Kerjasama Pemerintah Swasta (KPS) - Tri Sefrus (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
Commodity movement area of Jambi, Riau and West Sumatra eastern part transported by road transport with the same line, namely Padang - Solok. The transport flow reached 8158 vehicles with payloads reached 2,338,834 tons per year (Department of Communication and Information, 2011). The traffic flow is causing congestion and road damage. To that end, it is necessary to limit the load of freight trucks. One of them with modal shifts to rail. And one of the technical aspects to be considered, is taking into account the number of requests (estimated demand) in the long term. Estimates of origin destination matrix made by the method of Gravity types without limitation, by using secondary data from the Department of Transportation West Sumatra Province. From the estimation, predictable amount of freight that passes through Padang - Solok in 2015 amounted to 2.29512 million tons with a growth rate of 1.52% per year. So predictable amount of freight in 2040 amounted to 3.34632 million tons / year.